Failure analysis of hard disk drive components - Gee, Sheng Hin. (2008)
A new electrical tagging pattern, which applies a non-return-to zero scheme to directly translate the channel bits to magnetic transitions during the writing of the magnetic pattern around the defect is used. With the help of Kerr magneto-effect, the defective sector is effectively located for further failure analysis. This phenomenon involves an input plane-polarised light.